A Case Report of 29-Years-Old Man with Hypokalemic Periodic Paralysis - Rosi Dwi Mulyono; Hasyim (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Primary hypokalemic periodic paralysis is a rare neuromuscular disorder of episodic muscle weakness. The estimated prevalence is 1:100.000. Hypokalemia is a decrease in serum potassium level <3.5 mmol/L. Hypokalemia can cause periodic paralysis. Case: A 29-year-old man complained of sudden weakness in four limbs, flaccid, proximal-dominant. Weakness in both legs on the first day, followed by weakness in both hands the next day. The patient ate a lot of rice 3 days before the attack. History of four limbs weakness 5 years ago. Upper limb motor strength was 4/3/3 | 3/3/4, and lower limb was 4/3/2 | 2/3/4. Potassium level was 2.59 mmol/L. Potassium correction therapy was performed with KCl 25 mEq in NaCl 0.9% 500cc at a rate of 20 TPM and KCl tablets 600mg/8 hours. The potassium level after the correction was 4.91 mmol/L. Motor strength returned to normal on the third day. Discussion: Our patient was diagnosed with hypokalemic periodic paralysis (HypoPP). The patient had moderate hypokalemia and returned to normal with a single correction. The leading cause of hypokalemia was suspected to be the underconsumption of potassium and overconsumption of carbohydrates. The patient's condition improved as potassium levels normalized. Conclusion: HypoPP is a rare neuromuscular disorder associated with hypokalemia, and the primary therapy is potassium correction. The cause of hypokalemia in this case is due to underconsumption of potassium and overconsumption of carbohydrates, but other causes of hypokalemia still need to be considered.